Evaluation of the Effect of Different Soil Surface Treatments in the Vineyard Inter-Row on the CO2 Emissions - Patrik Burg; Vladimír Mašán; Petra Zabloudilová; Miroslav Češpiva; Jana Burgová; Jindřiška Jeřábková; Adam Lipinski; Piotr Markowski (Agronomy)
In recent years, increasing efforts have been directed towards reducing greenhouse gas emissions from agriculturally managed soils to mitigate their negative environmental impacts. The total emissions released are influenced by the chosen farming practices, including soil surface treatment methods. While numerous studies have focused on arable cropping systems, research in permanent crops, such as vineyards, remains limited. For this reason, our study aimed to assess the effects of different soil surface management strategies in vineyard inter-rows on CO2 emissions. Five treatments were examined: cultivation to a depth of 70 mm (C70); cultivation to a depth of 150 mm (C150); compost application (50 t·ha−1) incorporated into the soil at 150 mm depth (C+C150); mulching with plant residues left on the soil surface (M) and an untreated control (Co). Results from two-year measurements indicated the highest CO2 emissions in the C+C150 treatment (42–76% higher) and C150 (34–53% higher) compared to the control (Co). The impact of soil surface treatment on CO2 emissions is further substantiated by cumulative values recorded over 120 days, ranging from 11–24 g C-CO2·m−2·h−1, corresponding to 9.64–21.03 Mg C-CO2·ha−1·y−1.